2010
DOI: 10.1007/s10551-010-0692-x
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Intellectual Capital Disclosure

Abstract: corporate governance, intangibles, board of directors, intellectual capital,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
194
6
24

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(259 citation statements)
references
References 60 publications
35
194
6
24
Order By: Relevance
“…Furthermore, Elzahar and Hussainey (2012) stated that the increased board size may lead to an increase in the number of directors who have a financial or accounting background, which could have a positive influence on corporate environmental disclosure (Elzahar and Hussainey 2012). Consistent with these arguments, the results of the empirical studies such as Janggu et al (2014), Ntim et al (2013), Jizi et al (2014), Haji (2012), Akhtaruddin et al (2009), Buniamin et al (2011), Sun et al (2010, Cheng and Courtenay (2006), Liao et al (2014), Allegrini and Greco (2013), Samaha et al (2015), Lim et al (2007), Kathyayini et al (2012), Hidalgo et al (2011) documented a positive relationship between the board size and the level of disclosure.…”
Section: Board Sizementioning
confidence: 77%
See 1 more Smart Citation
“…Furthermore, Elzahar and Hussainey (2012) stated that the increased board size may lead to an increase in the number of directors who have a financial or accounting background, which could have a positive influence on corporate environmental disclosure (Elzahar and Hussainey 2012). Consistent with these arguments, the results of the empirical studies such as Janggu et al (2014), Ntim et al (2013), Jizi et al (2014), Haji (2012), Akhtaruddin et al (2009), Buniamin et al (2011), Sun et al (2010, Cheng and Courtenay (2006), Liao et al (2014), Allegrini and Greco (2013), Samaha et al (2015), Lim et al (2007), Kathyayini et al (2012), Hidalgo et al (2011) documented a positive relationship between the board size and the level of disclosure.…”
Section: Board Sizementioning
confidence: 77%
“…In a similar vein, it is suggested that as the number of the directors on the board increases, the monitoring capacity of the board also increases, but this benefit may be outweighted by the incremental cost of poorer communication and a slower decision making process (John and Senbet 1998;Lipton and Lorsch 1992;Hidalgo et al 2011). Futhermore, Kathyayini et al (2012) state that decisions related to the content and extent environmental information disclosure need effective communication and coordination among board members.…”
Section: Board Sizementioning
confidence: 99%
“…Many previous studies have descriptively analyzed the amount of information supplied by companies in a given country, during a short period of time of one or two years (Abeysekera, 2010;Abeysekera & Guthrie, 2005;An, Davey, Eggleton, & Wang, 2015;Bozzolan et al, 2003;García-Meca et al, 2005;Goebel, 2015;Guthrie & Petty, 2000;Hidalgo et al, 2011;Li et al, 2008;Macagnan, 2009;Monclús et al, 2006;Oliveras et al, 2008;Tejedo-Romero & AlfaroCortés, 2014;Whiting & Miller, 2008;Yi & Davey, 2010).…”
Section: Spanish Regulation and Contextmentioning
confidence: 99%
“…Few studies have attempted to establish relationships between IC disclosure, ownership structure and CG (Abeysekera, 2010;Cerbioni & Parbonetti, 2007;Hidalgo, García-Meca, & Martínez, 2011;Li, Pike, & Haniffa, 2008;Rodrigues et al, 2017). Institutional and legal differences in individual countries, in particular their ownership structure and CG system (unitary or dual), can lead to significant variations in governance models and revealed information.…”
Section: Introductionmentioning
confidence: 99%
“…It can be broadly classified into (1) the research on factors which have an impact on intellectual capital disclosures (e.g. size of the organisation and industry type (Brüggen et al, 2009;Whiting & Woodcock, 2011), firm age (White et al, 2007;Sonnier et al, 2009), corporate governance (Li et al, 2008;Hidalgo et al, 2011;Haji & Ghazali, 2013), listing status (Williams, 2001)), and (2) the research which assesses the impact of intellectual capital disclosures on different areas of organisation's performance and its valuation. The latter research provides evidence on, for example, significant and positive effect of intellectual capital disclosures on market capitalization and firm value (Abdolmohammadi, 2005;Orens et al, 2009), the impact of intellectual capital disclosures on the reduction of information asymmetry (Orens et al, 2009;An et al, 2011) and (consequently) the impact of voluntary intellectual capital disclosures on the reduction of the cost of equity capital (Orens et al, 2009;Boujelbene & Affes, 2013;Mangena et al, 2010Mangena et al, , 2016.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%